2016
DOI: 10.18483/ijsci.1082
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality, Mycotoxins and Antinuntritional Factors in Quality Protein Maize-Based Supplementary Foods for Children in Tanzania

Abstract: Most complementary foods used for children in Tanzania are low in energy and nutrient content. In addition, they may contain contaminants such as mycotoxins and also antinutritional factors. The aim of this study was to determine nutritional quality of quality protein maize-based supplementary foods and levels of mycotoxins (fumonisins, aflatoxins) and antinutritional factors (phytates, tannins). Three composite diets were prepared from quality protein maize namely; quality protein maize-soybeans; quality prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The phytate content in all samples was found to exceed the tolerable level for human consumption. According to Onomi et al (2004), the tolerable level for phytate is 25 mg/100 g. Nonetheless, below this level the micronutrient losses are minimized (Maseta et al, 2016). The range of phytate found in this study was 59.47 -1176.80 g/100 g, Gibson et al (2010) reported phytate content of 600 mg/100 g in unrefined cereals and legumes-based complementary foods.…”
Section: Discussionmentioning
confidence: 51%
“…The phytate content in all samples was found to exceed the tolerable level for human consumption. According to Onomi et al (2004), the tolerable level for phytate is 25 mg/100 g. Nonetheless, below this level the micronutrient losses are minimized (Maseta et al, 2016). The range of phytate found in this study was 59.47 -1176.80 g/100 g, Gibson et al (2010) reported phytate content of 600 mg/100 g in unrefined cereals and legumes-based complementary foods.…”
Section: Discussionmentioning
confidence: 51%
“…The reduction in tannins by the dehulling process could be due to the removal of the hulls since most tannins are located in the hulls. The concentrations of tannins in the flour recorded in this study posed no health risk since the accepted lethal dose reported is 0.09% (Ifie and Emeruwa, 2011;Maseta et al, 2016). Tannins are high oligomeric molecules of polyphenol that occur in plants naturally (Adeoti et al, 2017).…”
Section: Resultsmentioning
confidence: 65%
“…Thapliyal et al (2014) reported a 14.39-20.87% reduction for chickpeas, and Wang et al (2008) reported a decrease of 5.3-8.0% in field peas due to dehulling. The concentrations of phytate in the flours were lower than the considered lethal amount to human health, 250 mg/100 g, reported in the literature (Nagel, 2010;Maseta et al, 2016). According to Kumar et al (2010), phytates, when at high levels in human foods, may limit the bioavailability and utilization of minerals such as iron, calcium, magnesium, and manganese by forming compounds that are insoluble and indigestible.…”
Section: Resultsmentioning
confidence: 88%
“…Tannin content ranged from 0.27 to 0.50%. The concentrations of tannin in the flours posed no health risk, since the reported safe level is 90 mg/100g" [26]; [27]. "Tannins are the oligometric higher molecular of polyphenols compound occurring naturally in plants" [28].…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…The amount of oxalate in the processed flour (0.21 -0.31 mg/100g), equally, could not be toxic under meal portion since they were lower than the safe level (15-30 g/100g food consumed) reported in literature for man [30]. Concentrations of phytate in the flours was 0.37 -7.42 mg/100g, and were lower than 250 mg/100g, the amount considered safe level to health [31]; [27]. This indicated that the concentration of phytate in the flour samples were of acceptable safe levels.…”
Section: Phytochemical Compositionmentioning
confidence: 99%